(3SfOGJ GdebGQVI hCMcGegG aj Gdabg GdESdGej (B:s (3OQGSI ebGQfI JWHjbjI (B/s - (3LHQ GSeGYjd, YeQ eUWais ((3YeGf(B: s (3OGQ GdfaGFS(B, s, 2006)
(3JYQja CShGb GdChQGb GdeGdjI hCMcGegG hJYQja GdeVGQHI hCMcGegG(B-(3JWHjbGJ GdeVGQHI GdMOjKI(B:(3SfOGJ GdebGQVI(B-(3JWHjbGJ GdeVGQHI GdMOjKI(B-(3SfOGJ GdebGQVI GdCQOfjI fehPLG(B-(3MLe JWHjb SfOGJ GdebGQVI hOhQgG GdEbJUGOj hGdJfehjs
Keywords: (3CMcGe GdebGQVIs; (3GdebGQVIs; (3SfOGJ GdebGQVIs